Thermally-Induced Actuations of Stimuli-Responsive, Bicompartmental Nanofibers for Decoupled Drug Release - Jung, Chan Woo; Lee, Jae Sang; Jalani, Ghulam; Hwang, Eun Young; Lim, Dong Woo (Frontiers in Chemistry, 2019)
Stimuli-responsive anisotropic microstructures and nanostructures with different physicochemical properties in discrete compartments, have been developed as advanced materials for drug delivery systems, tissue engineering, regenerative medicine, and biosensing applications. Moreover, their stimuli-triggered actuations would be of great interest for the introduction of the functionality of drug delivery reservoirs and tissue engineering scaffolds. In this study, stimuli-responsive bicompartmental nanofibers (BCNFs), with completely different polymer compositions, were prepared through electrohydrodynamic co-jetting with side-by-side needle geometry. One compartment with thermo-responsiveness was composed of methacrylated poly(N-isopropylacrylamide-co-allylamine hydrochloride) (poly(NIPAM-co-AAh)), while the counter compartment was made of poly(ethylene glycol) dimethacrylates (PEGDMA). Both methacrylated poly(NIPAM-co-AAh) and PEGDMA in distinct compartments were chemically crosslinked in a solid phase by UV irradiation and swelled under aqueous conditions, because of the hydrophilicity of both poly(NIPAM-co-AAh) and PEGDMA. As the temperature increased, BCNFs maintained a clear interface between compartments and showed thermally-induced actuation at the nanoscale due to the collapsed poly(NIPAM-co-AAh) compartment under the PEGDMA compartment of identical dimensions. Different model drugs, bovine serum albumin, and dexamethasone phosphate were alternately loaded into each compartment and released at different rates depending on the temperature and molecular weight of the drugs. These BCNFs, as intelligent nanomaterials, have great potential as tissue engineering scaffolds and multi-modal drug delivery reservoirs with stimuli-triggered actuation and decoupled drug release.